2000
DOI: 10.1038/sj.ijir.3900549
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and neuronal-derived nitric oxide mediated relaxation of corpus cavernosal smooth muscle in a rat, in vitro, model of erectile function

Abstract: We set out to establish a simple, reproducible, rat in vitro model of erectile function and to use this to demonstrate the functional importance of both neuronal-and endothelial-derived nitric oxide within this animal.Two corpora cavernosal smooth muscle strips were harvested from sexually mature male Wistar rats and mounted in an organ bath for measurement of isometric tension. Following contraction with noradrenaline the strips were relaxed by the addition of either acetylcholine or sodium nitroprusside. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…We were surprised to find that isolated corporal tissue from both wild-type and NOS-deleted animals showed similar responses to electrical stimulation (Burnett et al, 1996;Hurt et al, 2006). Functional studies support the occurrence and importance of eNOS in human cavernosal tissue (Andersson and Wagner, 1995;Musicki and Burnett, 2006), and this seems to be the case also in rat (Cartledge et al, 2000b) and mouse (Mizusawa et al, 2001) CC.…”
Section: J Nitric Oxide and Cgmp Signalingmentioning
confidence: 97%
“…We were surprised to find that isolated corporal tissue from both wild-type and NOS-deleted animals showed similar responses to electrical stimulation (Burnett et al, 1996;Hurt et al, 2006). Functional studies support the occurrence and importance of eNOS in human cavernosal tissue (Andersson and Wagner, 1995;Musicki and Burnett, 2006), and this seems to be the case also in rat (Cartledge et al, 2000b) and mouse (Mizusawa et al, 2001) CC.…”
Section: J Nitric Oxide and Cgmp Signalingmentioning
confidence: 97%
“…Functional studies support the occurrence and importance of eNOS in cavernous tissue ( Anderson and Wagner, 1995;Cartledge et al, 2000). eNOS expression and eNOS activity increase during erection.…”
Section: Discussionmentioning
confidence: 81%
“…Another study demonstrated that there is ~13% decrease in the gene expression of nNOS in the penises of aged rats (17). In addition, increasing evidence has shown that endothelial and neuronal-derived nitric oxide acts as an important mediator of corpus cavernosal smooth-muscle relaxation and penile erection in rats with ED (18). nNOS was also shown to be involved in mediating initiation as well as maintenance of penile erection via cyclic adenosine monophosphate-dependent phosphorylation (9).…”
Section: Discussionmentioning
confidence: 99%